POSSIBILITIES OF USING STABLE ISOTOPES FOR IDENTIFICATION OF GEOGRAPHICAL ORIGIN OF MEAT AND MEAT PRODUCTS. A REVIEW - N. A. Gorbunova (Теория и практика переработки мяса, 2018)
of geographical origin of raw materials and animal-derived products to exclude a possibility of their falsification is quite a complex task,  which requires searching for reliable criteria of identification that  account for an effect of the geoclimatic and anthropogenic factors.  One of the methods for revealing falsification of geographical origin  of food including meat products is a method of analysis of stable  isotopes (2H/1H, 18O/16O, 15N/14N, 13C/12C) and several other  elements. The review describes the main theoretical provisions of  stable isotope analysis and their fractionation, presents the results of the investigation of the isotopic composition of meat raw materials  and products of animal origin for verification of their geographical  origin and feeding systems that differ largely in the content of C3  and C4 plants in the animal diet. Analysis of the C, N and S stable  isotope ratio has a significant potential for authentication of meat raw materials and verification of the origin. In addition, it can be used to detect differences between very similar agricultural production systems, even if the underlying mechanisms are not fully elucidated.